The relationship between training and competition load characteristics of female boxers—a case study based on collegiate boxers - Qinglou Xu; Qinglou Xu; Zhongjie Wang; Lei Liu; Ruiqiu Mao; Changjin Xi; Guoxin Shi (Frontiers in Psychology)
IntroductionThis study examines the relationships between external and internal loads in female collegiate boxers during training and competition, focusing on variations during menstruation and non-menstruation periods. It also evaluates the effectiveness of different monitoring techniques in these contexts, providing guidance for coaches and athletes in load management.MethodsTwenty-one healthy female collegiate boxers participated, recording data across 18 training sessions and 6 competitions over six weeks. The metrics collected included session-RPE (sRPE), Banister’s Trimp, Stagno’s Trimp, moving distance, high-intensity moving distance, physical load, and the ratio of body weight loss. Pearson correlation analyses were applied.ResultsCorrelation analysis revealed that internal and external loads are consistently positively correlated during training and competition. Apart from the training phase, where the correlation between sRPE and Stagno’s Trimp was not statistically significant (r = 0.181, p > 0.05), correlations between sRPE and other indicators during both training and competition showed medium to high strength (r = 0.426 ~ 0.880, p < 0.05). During menstruation, the correlations of all metrics were lower than in non-menstruation periods, except sRPE with Banister’s Trimp.DiscussionThe study highlights that the subjective load sRPE can effectively predict and assess the internal load of female boxers, and is more sensitive to internal loads regardless of menstruation status. However, its application to external loads is limited, and objective measurements are recommended during menstruation.